(untitled) (Texas Journal of Medical Science, 2024)
The Emergency Surgery Department of TMA performed 206 laparoscopic operations for acute appendicitis. The duration of laparoscopic operations for acute appendicitisperformed with and without the napeto algorithm was compared. The method developed by us for calculating the optimal placement of trocars allows us to model possible variants of intraoperative geometry individually for each patient before surgery and choose the most optimal arrangement of manipulative trocars. МетодThe calculation method is simple and неrequires no additionalоequipment.